Uncovering Factors Leading To Customer Loyalty in The Optical Industry - Toh, Thiam Seen (2017)
Relationship marketing has been closely related to the roles of relationship quality and customer loyalty in sustaining long term business goal which is to be profitable. The optical industry has been weakly represented in the literature and hence the purpose of this study is to demonstrate the differential effects of four important factors namely technical quality, functional quality, product quality and physical environment quality on satisfaction, trust and customer loyalty in the context of an optical professional service. This study accumulated 220 survey responses from mall shoppers and multiple regression, mediation and moderation techniques were used to analyze the results. The results highlighted that all four factors have significant impact on customer loyalty in particular product quality and physical environment quality. Switching barriers have a significant negative effect on satisfaction- loyalty relationship. Future research could consider to further explore the research outcome in a longitudinal study and look into other additional constructs that may play a role in moderating the relationship. This study provides important understanding to managers on areas to improve and look into in order to increase probability of customers being loyal to the store.